INSTITUTIONAL MECHANISMS OF SUPPORTING OF INNOVATIVE ECONOMY IN RUSSIA - Yu. S. Bogachyov; A. M. Octiabrskiy; T. G. Popadyuk; L. V. Vasilyeva (Финансы: теория и практика)
The article analyzed institutional mechanisms of supporting “growth points” of the innovative economy in Russia, which strategically positions itself in the global market as one of the world technology leaders.In Russia nowadays, there is no organizational structure where the level of concentration and reproduction of intellectual resources would create a potential of advanced manufacturing technologies on the principles of the 6th technological mode. Therefore, there is an urge in Russia to create institutional conditions for the formation and functioning of points of growth of an innovative economy based on advanced manufacturing technologies.